2019
DOI: 10.1021/acs.jafc.9b00449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propiconazole on the Lipid Metabolism of Zebrafish Embryos (Danio rerio)

Abstract: Propiconazole is a triazole fungicide that has been widely used in agriculture and has been detected in the aquatic environment. This study aimed to investigate the effects of propiconazole exposure on lipid metabolism in the early life stages of zebrafish for 120 h postfertilization (hpf). Using the early life stages of zebrafish to address scientific questions is lower in cost, more efficient, and suitable to meeting current legislation than those in other traditional fish species. Exposure to propiconazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 71 publications
(115 reference statements)
1
15
0
Order By: Relevance
“…Hernández-Moreno et al (2011) argue that there is a great variability in the results of LC50 found for different species and even within the same species, therefore, comparisons of results should be interpreted with caution to avoid erroneous conclusions possibly due to the applied test, the testing conditions, stage of life of the exposed organisms, among other factors. However, the fact is that concentrations found in the environment of 12.90 mg L − 1 can be very harmful to sh (Teng et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernández-Moreno et al (2011) argue that there is a great variability in the results of LC50 found for different species and even within the same species, therefore, comparisons of results should be interpreted with caution to avoid erroneous conclusions possibly due to the applied test, the testing conditions, stage of life of the exposed organisms, among other factors. However, the fact is that concentrations found in the environment of 12.90 mg L − 1 can be very harmful to sh (Teng et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The zebra sh, Danio rerio, is the model sh most used in bioassays on genetics, neurophysiology, and biomedicine (Amsterdam and Hopkins 2006;Teng et al 2019). Other important aspect in zebra sh is the transparent embryo for an easy teratogenesis assessment (Keshari et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the hazard classification, propiconazole is classified as reproductive toxicity 1B category and belongs to endocrine disrupting substances [4]. Related studies have confirmed that propiconazole can result in genetic toxicity, liver toxicity and growth toxicity [5][6][7]. The U.S. Environmental Protection Agency has included propiconazole in the list of possible human carcinogens [8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, its high homology with mammalian genes is favorable for assessing developmental toxicity and neurotoxicity of chemical substances (Jia et al, 2020;Shen et al, 2020b). Besides, using zebra sh embryos to address scienti c questions is more suitable to meet current legislation (Teng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%